(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This study aims to assess the contribution of the application of financial resources and the impact of size on firm performance in the Indian banking industry. A total of nine variables have been taken for the study, namely, return on investment, return on advances, return on fixed assets, number of employees, number of branches, etc. The study applies panel regression to analyze the data of 10 public sector banks and 10 private sector banks for five years from 2016 to 2020. The results confirm the impact of changes in size on the performance of the banks. Out of all the nine variables, an increase in current assets, advances, and employee number was found to have a positive impact on bank performance in terms of ROA and ROE whereas any increase in branch spread and assets apart from advances, fixed assets, current assets, and investments is expected to decrease the profit potential of the firms.